2007
DOI: 10.3732/ajb.94.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Ancient paralogy in the cpDNA trnL‐F region in Annonaceae: implications for plant molecular systematics

Abstract: The plastid trnL-F region has proved useful in molecular phylogenetic studies addressing diverse evolutionary questions from biogeographic history to character evolution in a broad range of plant groups. An important assumption for phylogenetic reconstruction is that data used in combined analyses contain the same phylogenetic signal. The trnL-F region is often used in combined analyses of multiple chloroplast markers. These markers are assumed to contain congruent phylogenetic signal due to lack of recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 60 publications
(105 reference statements)
0
42
0
2
Order By: Relevance
“…Similarly, differentiation within the genus Populus failed using trnLF [38]. Nevertheless, there are other examples for successful use of this marker in molecular systematics [39,40] and citations therein) and for unraveling of the phylogeny of different plant species [41]. Similarly, trnCD and trnDT have been used in comprehensive studies of chloroplast DNA diversity in European white oaks [42][43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, differentiation within the genus Populus failed using trnLF [38]. Nevertheless, there are other examples for successful use of this marker in molecular systematics [39,40] and citations therein) and for unraveling of the phylogeny of different plant species [41]. Similarly, trnCD and trnDT have been used in comprehensive studies of chloroplast DNA diversity in European white oaks [42][43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of plastid trnF pseudogenes in seed plants is extremely rare (Schmickl et al 2009). They have been only described from a few plant genera in Asteraceae (Vijverberg and Bachmann 1999), Annonaceae (Pirie et al 2007), Brassicaceae ) and Juncaceae (Drábkova et al 2004), but they have not been reported in Solanaceae.…”
Section: Introductionmentioning
confidence: 96%
“…Missaoui et al (2006) also found polymorphism for the trnL (UAA) chloroplastic marker associated with upland and lowland ecotypes. The trnL UAA intron region is in the chloroplasts of all plants (Pirie et al, 2007). It is part of the chloroplast DNA and is transferred through the maternal parent (Martinez-Reyna et al, 2001).…”
Section: Introductionmentioning
confidence: 99%